Interventions of Body Image Disorder among Adolescent: A Literature Review - Hidayati, Nur Oktavia; Sutini, Titin; Nurhidayah, Ikeu (GLOBAL HEALTH SCIENCE GROUP, 2024)
Adolescence represents the transition from childhood to adulthood and is associated with physical and social changes. Adolescence is a critical period in the development of body image. Critical events or sequences of events such as temptation and rejection can cause body image misperceptions or disturbances. The aim of this literature review is to identify interventions that nurses can do to overcome the problem of body image disorders in adolescents. The method used in the search is the literature study method with a series that includes searching for journal articles using certain keywords from the PubMed and CINAHL databases in the 2018 - 2023 period. The search results obtained 445 articles discussing body image disturbance interventions in adolescents, but only five articles that can meet the inclusion criteria. The results of the study showed that five interventions can be used to treat body image disorders in adolescents, namely application-based interventions (BodiMojo), Healthy Body Image (HBI) interventions, puberty education based on health belief models, application-based Cognitive-behavioral Therapy (CBT), and universal wellness programs. The five interventions proved to be effective in overcoming body image disorders in adolescents.